Changes in intraocular pressure and horizontal pupil diameter during use of topical mydriatics in the canine eye - Kovalcuka, Liga (Open Vet J, 2017)
The objective of this study was to determine the effects of topical 0.5% tropicamide, 1% atropine sulphate and 10% phenylephrine hydrochloride ophthalmic solutions on intraocular pressure (IOP) and horizontal pupil diameter (HPD) in the dog during the first hour after treatment. Forty clinically and ophthalmologically normal canine patients (between the ages of 2 and 6 years) of varying breed and sex were used in this study. Animals were randomly divided into four groups of ten and given one drop of tropicamide, atropine, phenylephrine or saline into one eye. IOP and HPD were measured in both eyes every 5 minutes for 60 minutes. Tropicamide increased IOP by 8.8±4.0 mmHg 35 minutes post-treatment compared to pre-treatment (P<0.01) only in treated eye. IOP in the contralateral eye did not increase. With atropine the maximum increase in IOP was 2.6±2.8 mmHg at 20 minutes post treatment in the treated eye (P<0.01). IOP in the contralateral eye did not increase. Phenylephrine increased IOP by 2.3±2.1 mmHg (P<0.05) 10 minutes after treatment. Also in the untreated eye IOP increased by 2.3±2.1 mmHg, 20 minutes post-treatment. Maximum HPD in eyes treated with tropicamide occurred at 55 minutes and with atropine at 60 minutes. There were no HPD changes in the contralateral, untreated eye. Topical 10% phenylephrine showed maximal pupil dilation 60 minutes after treatment, but the HPD of the – untreated eye slightly decreased at 15 minutes, but this change only reached statistical significance at 40 min post- treatment (P<0.05). Normal saline showed no influence on IOP or HPD. The drugs investigated here show a significant increase in IOP after mydriatics.